Weed anatomy - Kraehmer, Hansjoerg; Baur, Peter, 1965- (Chichester, West Sussex, UK ; Ames, Iowa, USA : Wiley-Blackwell, 2013)
"Essential for all weed scientists, this book provides fully comprehensive coverage, including the world's fifty commercially most important species, with detailed, full color photographs throughout. Beginning with a general overview of weed anatomy, structured in a way similar to other classical plant anatomy textbooks, this book discusses monocots, dicots, brackens and horsetails with special reference to their anatomy. Plant scientists will appreciate the depth of detail found in this book"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Weeds -- Anatomy; Electronic books